Imagining Xerxes : ancient perspectives on a Persian king - Bridges, Emma (Bloomsbury studies in classical reception., 2015)
Xerxes, the Persian king who invaded Greece in 480 BC, quickly earned a notoriety that endured throughout antiquity and beyond. The Greeks' historical encounter with this eastern king â€" which resulted, against overwhelming odds, in the defeat of the Persian army â€" has inspired a series of literary responses to Xerxes in which he is variously portrayed as the archetypal destructive and enslaving aggressor, as the epitome of arrogance and impiety, or as a figure synonymous with the exoticism and luxury of the Persian court. Imagining Xerxes is a transhistorical analysis that explores the r.